Categorization and Characterization of Activities Designed to Help Health-care Professionals Involved in Hepatitis Care Increase Their Awareness of the Disease: The Classification of Hepatitis Medical Care Coordinators - Kanzaki, Naruyo (Intern Med, 2019)
OBJECTIVE: This study aimed to investigate the current state of the activities performed by hepatitis medical care coordinators, categorize coordinators according to the activities they perform, and determine the backgrounds of these coordinators. METHODS: A self-administered questionnaire survey was completed by 414 coordinators. The surveyed items included gender, occupation, activity items performed, and barriers that inhibited the performance of these activities. A hierarchical cluster analysis was applied, and cases were classified based on the contents of the activities in question. RESULTS: The coordinators were classified into four groups (A-D). Group A, consisting primarily of public health nurses, was classified as “the type that conducted activities aimed at providing information and recommendations.” Group B, which included registered dieticians and clerks, was classified as “the type that uses multidisciplinary collaboration to perform their tasks.” Group C, which included clinical nurses, was classified as “the type that was more likely to perform activities as leaders in an organization.” Group D, consisting primarily of pharmacists, was classified as “the type that promoted activities centered on providing instructions regarding medication dosage and administration.” CONCLUSION: Our study showed that coordinators' professional skills and abilities are reflected in the contents of the activities they conduct, and that, to adequately perform their roles, they must acquire skills in addition to those required in their original occupations. To implement high-quality hepatitis countermeasures, there is a need to foster an environment that facilitates cooperation between coordinators, as well as relationship-building.